Influence of hard, artificial grass and clay court surfaces on wheelchair tennis players' mobility-a case study - Alejandro Sánchez-Pay; David Sanz-Rivas (European Federation of Adapted Physical Activity, 2021)
Wheelchair mobility is an important factor for success in wheelchair tennis. Tennis matches can be played on different surfaces, so the aim of the present study was to analyse the influence of court surface on wheelchair tennis mobility. Four male wheelchair tennis players (age = 33.75 ± 12.33 years) performed two tests (20 m sprint and agility t-test) on three official court surfaces (hard, artificial grass and clay). Photocell gates were used to record time and ascertain sprint and turn ability of the wheelchair tennis players. ANOVA test with post hoc pairwise comparisons were conducted to compare the mean differences among surfaces. Following the analysis, the wheelchair tennis players moved faster on hard or clay surfaces than on artificial grass although no statistically significant differences in the 20 m sprint and agility t-test between each of the three surfaces were found (p > 0.05). Moreover, the surface seems to affect mobility more, with respect to turns than in linear locomotion, although more research is needed on this aspect. The playing surfaces may need to be an extra variable in planning performance related activities such as techniques and tactics.